Developing Metacognitive ESP Module to Enhance Motivation for Riau Islands Tourism Village Guides - Siska Amelia Maldin; Tito Pratama (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
Tourism village guides in the Riau Islands increasingly require advanced English communication skills to meet the demands of authentic guiding contexts, alongside effective learning strategies that support professional performance. However, many guides continue to encounter challenges such as limited vocabulary range, inconsistent fluency, low communicative confidence, and inadequate self-regulatory learning skills. These conditions highlight the necessity for instructional materials that integrate linguistic development with metacognitive awareness. This study aims to design and evaluate a metacognition-based English for Specific Purposes (ESP) module to enhance learning motivation and learner autonomy among tourism village guides. Employing a quantitative research and development approach, the study involved 70 participants in the needs analysis phase, followed by module development, expert validation, and a two-week implementation with five selected guides. Data were collected through pre- and post-tests and perception questionnaires. The findings reveal limited engagement in planning, monitoring, and self-evaluation strategies prior to the intervention. Statistical analyses indicate significant improvements in metacognitive awareness and learning motivation following the module’s implementation. Expert review further confirmed the module’s validity, authenticity, and pedagogical relevance.